Kebijakan pengelolaan ekosistem laut akibat pertambangan timah di Provinsi Bangka Belitung - Rismika, Tanti; Purnomo, Eko Priyo (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
Bangka Regency is one of the regions that has the potential of natural resources with abundant tin mineral content. Initially tin mining was mostly carried out on the land, but with the development of the times and depletion of tin sources on the ground began to shift towards the sea. Environmental problems arising from marine mining are increasing, which is exacerbating damage to marine ecosystems, damaged coral reefs, and a decline in fishing production with this decreasing fishermen's income. This study aims to determine the policies of the Bangka Regency Government in the management of marine ecosystems and to know the impact of damage to marine ecosystems due to tin mining. This research uses descriptive qualitative approach method aims to describe the phenomena that occur at this time. The results of this study describe the contents of the marine mining policy as regulated No. 32 of 2009 concerning Environmental Protection and Management which aims to ensure the survival of living things and the preservation of ecosystems; Policy benefits; Management of Sea Water Pollution Control which includes: Environmental management objectives, Management Location, Time of Management and Implementers of Management and Management of B3 Waste; and Sea Water Quality Measurement Results.DOI: https://doi.org/10.26905/pjiap.v4i1.2539